1983
DOI: 10.1177/001872088302500107
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Extended Practice on the Evaluation of Visual Display Codes

Abstract: A series of nine experiments are reported in which highly practiced subjects were used to investigate the use of letters, digits, familiar geometric shapes, and colored dots as coding dimensions in visual displays. These experiments used single-code and dual-code displays in three isolated tasks (choice reaction, search and locate, and identification-memory) and in a multiple task that combined the three tasks in an irregularly alternating sequence. The results of these experiments provided no basis for conclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

1989
1989
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(13 citation statements)
references
References 6 publications
0
13
0
Order By: Relevance
“…Not only does familiarity improve comprehension (e.g., Cahill, 1975), it also affects the usability of symbols, as has been shown by the considerable increase in users' performance after learning symbol-function relationships (e.g., Montagne, 2013). Additionally, it has been shown that familiarity and experience with a symbol reduces the impacts that other variables (e.g., concreteness level or the use of color) have on its comprehension (e.g., Christ & Corso, 1982;Isherwood, McDougall, & Curry, 2007;Stammers, George, & Carey, 1989). Thus, familiarity appears to be a key attribute for understanding symbols.…”
Section: Dimensions Of Interestmentioning
confidence: 95%
“…Not only does familiarity improve comprehension (e.g., Cahill, 1975), it also affects the usability of symbols, as has been shown by the considerable increase in users' performance after learning symbol-function relationships (e.g., Montagne, 2013). Additionally, it has been shown that familiarity and experience with a symbol reduces the impacts that other variables (e.g., concreteness level or the use of color) have on its comprehension (e.g., Christ & Corso, 1982;Isherwood, McDougall, & Curry, 2007;Stammers, George, & Carey, 1989). Thus, familiarity appears to be a key attribute for understanding symbols.…”
Section: Dimensions Of Interestmentioning
confidence: 95%
“…For example, performance differences between concrete and abstract symbols have been found to lessen with familiarity (Arend et al, 1987;Stammers et al, 1989). Similarly, the beneficial effects ofuse of color in displays has been found to diminish over time as novice users become more expert (Christ & Corso, 1982). Despite such findings, it is interesting to note that although overall performance may improve in response to familiar complex and simple symbols, response times remain slower to complex symbols even after they have been learned (Byrne, 1993).…”
Section: Concreteness and Meaningfulness Other Research-mentioning
confidence: 99%
“…Performance will depend on several important factors: (1) the nature of the mapping from objects to symbols, (2) familiarity and training, and (3) discriminability (Christ and Corso, 1983;Geiselman, Landee, and Christen, 1982).…”
Section: £:■■■!mentioning
confidence: 99%